Aging Impairs Cerebrovascular Reactivity at Preserved Resting Cerebral Arteriolar Tone and Vascular Density in the Laboratory Rat - Bálint, Armand R.; Puskás, Tamás; Menyhárt, Ákos; Kozák, Gábor; Szenti, Imre; Kónya, Zoltán; Marek, Tamás; Bari, Ferenc; Farkas, Eszter (Frontiers in Aging Neuroscience, 2019)
The age-related (mal)adaptive modifications of the cerebral microvascular system have been implicated in cognitive impairment and worse outcome after ischemic stroke. The magnitude of the hyperemic response to spreading depolarization (SD), a recognized principle of ischemic lesion development has also been found reduced by aging. Here we set out to investigate whether the SD-coupled reactivity of the pial arterioles is subject to aging, and whether concomitant vascular rarefaction may contribute to the age-related insufficiency of the cerebral blood flow (CBF) response. CBF was assessed with laser-speckle contrast analysis (LASCA), and the tone adjustment of pial arterioles was followed with intrinsic optical signal (IOS) imaging at green light illumination through a closed cranial window created over the parietal cortex of isoflurane anesthetized young (2 month old) and old (18 month old) male Sprague-Dawley rats. Global forebrain ischemia and later reperfusion were induced by the bilateral occlusion and later release of both common carotid arteries. SDs were elicited repeatedly with topical 1M KCl. Pial vascular density was measured in green IOS images of the brain surface, while the density and resting diameter of the cortical penetrating vasculature was estimated with micro-computed tomography of paraformaldehyde-fixed cortical samples. Whilst pial arteriolar dilation in response to SD or ischemia induction were found reduced in the old rat brain, the density and resting diameter of pial cortical vessels, and the degree of SD-related oligemia emerged as variables unaffected by age in our experiments. Spatial flow distribution analysis identified an age-related shift to a greater representation of higher flow ranges in the reperfused cortex. According to our data, impairment of functional arteriolar dilation, at preserved vascular density and resting vascular tone, may be implicated in the age-related deficit of the CBF response to SD, and possibly in the reduced efficacy of neurovascular coupling in the aging brain. SD has been recognized as a potent pathophysiological contributor to ischemic lesion expansion, in part because of the insufficiency of the associated CBF response. Therefore, the age-related impairment of cerebral vasoreactivity as shown here is suggested to contribute to the age-related acceleration of ischemic lesion development.